Incomplete Kawasaki Disease in an Adult South Asian Patient - Neetu Boodoosingh MBBS; Rajeev Seecheran MBBS; Saleem Varachhia MBBS; Narine Mack MBBS; Vinay Minocha MBBS; Stanley Giddings MBBS; Naveen Anand Seecheran MBBS, MSc, FACC, FESC (SAGE Publishing, 2018)
Kawasaki disease is an acute multisystemic vasculitis occurring predominantly in children and rarely in adults, with sequelae of potentially life-threatening coronary artery aneurysms. "Incomplete" Kawasaki disease is a novel concept and considered a diagnosis of exclusion as it alludes to patients with fever lasting ⩾5 days and 2 or 3 clinical criteria without another reasonable explanation for the illness. The multidisciplinary team should be vigilant for this oligosymptomatic clinical presentation, specifically within this subgroup despite age and ethnicity, and the syndrome should be considered as a differential diagnosis in challenging cases presenting as infectious or autoimmune disease.